Implications of Diminishing Lifespan Marginal Utility for Valuing Equity in Cost-Effectiveness Analysis - R. Scott Braithwaite (MDM Policy & Practice)
Introduction. Diminishing marginal lifespan utility (DMLU) implies that a particular lifespan increment (e.g., 1 life-year) confers lesser marginal utility if added to longer lifespans (e.g., 90 y to 91 y) than to shorter lifespans (e.g., 60 y to 61 y) if quality of life is unchanged. Because DMLU is difficult to disambiguate from discounting, risk attitude, and other elements of utility “curvature,” it is poorly characterized. However, the imperative to consider equity in cost-effectiveness analysis (CEA) renders its characterization more important. Methods. I add certainty to the characterization of DMLU through literature review and illustrative example. The literature review synthesizes stated preference studies of utility curvature that exclude risk or probability. The example compares alternative valuations of approaches to reduce inequality in cystic fibrosis outcomes between US centers serving mostly White patients and centers serving mostly non-Black Hispanic patients, with versus without DMLU. Results. The existence of DMLU is likely, and empirical data support its relevance over typical CEA time horizons. The imperative to consider equity in CEA magnifies the importance of DMLU for several reasons. First, intergenerational CEAs require lower discount rates that are less likely to incidentally absorb DMLU. Second, DMLU is incompatible with the use of absolute measures of inequality aversion. Third, DMLU may bias the interpretation of relative measures of inequality aversion toward prioritarianism. Finally, not considering DMLU implicitly biases life-year–based metrics against equity. Conclusion. DMLU is likely to exist, can benefit from additional characterization, and may merit inclusion in CEA alongside discounting. Omitting consideration of DMLU will sometimes confer an antiequity bias and may affect the interpretation of CEAs incorporating inequality aversion. Highlights Diminishing marginal lifespan utility (DMLU) means that the value of extending lifespan may differ based on the duration of life already lived. DMLU is not typically considered in cost-effectiveness analyses. Not considering DMLU may bias cost-effectiveness analyses against equity. Not considering DMLU may reduce the accuracy of distributive cost-effectiveness analyses and other approaches to consider equity along with efficiency.